1997 CPER pasture treatment map - Central Plains Experimental Range, mapmaker (Colorado State University. Libraries, 1997)
Sections include: privately owned and operated, two year old heifers, study steers, stocker steers, stocker heifers, yearling breeders, replacement heifers, and winter pastures.
Central Plains Experimental Range 1997
The Long Term Ecological Research (LTER) project was established on the USDA, ARS Central Plains Experimental Range (CPER) on 1982. The CPER managed the research site and maintained the site as working rangelands in cooperation with the Crow Valley Livestock Association. CPER Pasture treatment maps are a record of the grazing regimes that were implemented in the pastures over time. SGS-LTER researchers conducted ecological field research (1982-2014) that focused on spatial and temporal patterns of ecosystem structure and function at the CPER and across the shortgrass steppe region. Research was concentrated in 5 areas: soil water; primary production; population and community dynamics; organic matter accumulation and nutrient dynamics; and disturbances with grazing regimes incorporated as a study treatment in many cases.
The SGS-LTER research site was established in 1980 by researchers at Colorado State University as part of a network of long-term research sites within the US LTER Network, supported by the National Science Foundation. Scientists within the Natural Resource Ecology Lab, Department of Forest and Rangeland Stewardship, Department of Soil and Crop Sciences, and Biology Department at CSU, California State Fullerton, USDA Agricultural Research Service, University of Northern Colorado, and the University of Wyoming, among others, have contributed to our understanding of the structure and functions of the shortgrass steppe and other diverse ecosystems across the network while maintaining a common mission and sharing expertise, data and infrastructure.
Keywords: pastures; grazing regimes; long term ecological research; shortgrass steppe; grassland ecology; Pawnee National Grassland; Central Plains Experimental Range